GroEL accelerates the refolding of hen lysozyme without changing its folding mechanism. - Coyle, J; Texter, F; Ashcroft, A; Masselos, D; Robinson, C; Radford, SE (1999)
The chaperonin GroEL binds folding intermediates of four-disulfidehen lysozyme transiently within its central cavity. Using stopped flow fluorescence we show that GroEL binds early intermediates in folding and accelerates the slow kinetic phase that reflects the reversal of non-native interactions involving tryptophan residues and the formation of the native state. Pulsed hydrogen exchange monitored by electrospray ionization mass spectrometry demonstrates that GroEL does not alter the folding mechanism, nor are protected species unfolded by the chaperonin. The data suggest a mechanism for GroEL-assisted folding in which the reorganization of non-native tertiary interactions is facilitated but domain folding is unperturbed.